The Psychology of Spirituality and Religion in Health Care - De Vries, Jan (Springer, 2019)
This chapter explores psychological aspects of spirituality. After an introduction to the psychology of spirituality and religion, the evolutionary psychological basis of transcendent belief is explored. A novel model is proposed based on the idea that ‘believing’ information from trusted sources was advantageous and possibly adaptive in our evolutionary history, which has facilitated the development of spirituality within the human species across the globe. The essential elements of this model are (a) believing as knowledge transmission, (b) believing as motivation or drive and (c) spiritual and religious beliefs as the basis for community (beyond kinship). These factors are further examined in relation to their benefits in health care today.
Spirituality in Healthcare: Perspectives for Innovative Practice
Keywords: spirituality and psychology; Relationships